Organisation de la post-catastrophe après Irma à Saint-Martin - Annabelle Moatty; Delphine Grancher; Clément Virmoux; Julien Cavero (EchoGéo)
On 3 September 2017, as cyclone Irma approaches Saint-Martin, the rectorate postponed sine die the school start for 8 000 students registered in public schools and 900 national education staff. As the cyclone damaged a majority of buildings and infrastructure (including schools), some of the island's pupils did not attend school for two months. In this work, we propose to consider the stories of adolescents as data likely to feed the post-disaster feedback. Our goal is to understand the experiences of adolescents and to characterize the actions they carried out in the post-crisis period. If their role is recognized, then their actions and implementation contexts need to be clarified.